The Role of Sustainability in Innovation Networks to Enhance SME Competitiveness: An Integrative Framework Based on PRISMA and Bibliometric Mapping - Pardiyono, Ragil; Moengin, Parwadi; Suryadi, Kadarsah; Mardi Safitri, Dian (Spektrum Industri, 2026)
Small and medium-sized enterprises (SMEs) play a critical role in economic development; however, their competitiveness remains constrained by fragmented integration of sustainability and innovation practices. Previous studies examine direct relationships between sustainability and competitiveness, without sufficiently explaining how innovation networks and policy environments interact within this relationship. This study addresses this gap by developing an integrative understanding of the role of sustainability in innovation networks to enhance SME competitiveness. This research employs a Systematic Literature Review (SLR) based on PRISMA 2020 guidelines, combined with bibliometric analysis using VOS viewer. The literature search initially identified 5,393 articles from the ScienceDirect database, of which 59 met the inclusion criteria for final analysis. The results reveal four main thematic clusters: (1) sustainability-oriented innovation, (2) internal firm capabilities, (3) innovation networks and national innovation systems, and (4) policy and digital transformation. The findings indicate that SME competitiveness emerges from the interaction between internal capabilities, collaborative networks, and institutional support, with sustainability acting as both a driver and outcome of innovation processes. This study contributes theoretically by proposing an integrative framework that extends prior literature by incorporating innovation networks as mediating factors and policy digital environments as enabling mechanisms. Methodologically, it demonstrates the value of combining PRISMA-based SLR with bibliometric mapping to systematically identify research patterns and gaps. Practically, the findings suggest that strengthening sustainability-oriented innovation and innovation networks, supported by appropriate policy and digital infrastructure, may enhance SME competitiveness in the evolving green and digital economy.